Структура та типологія запорозько-донських конфліктів в приазовських землях у 1743–1775 рр. - Полторак, В. (Чорноморська минувшина, 2014)
Системний аналіз усієї сукупності конфліктів дозволяє визначити не лише механізми виникнення та ескалації конфліктної ситуації, але й їхні функції. Поряд із деструктивними функціями, які є досить очевидними, кожен міжкозацький конфлікт ніс в собі можливість конструктивного вирішення проблем, що виникали у суспільному житті. Так, виділимо наступні позитивні функції запорозько-донських конфліктів: інформаційна; охоронна; інтегративна; нормо-утворювальна (внаслідок розв’язання низки конфліктів, зокрема, у 1746-1752 рр. відбулась переоцінка норм і цінностей міжкозацьких взаємин, що призвело до загального їх поліпшення); стимулююча (конфлікти надали стимул розвиткові системи управління всередині козацьких спільнот, стали рушійною силою змін у регіональній політиці та скоригували їх ставлення до центральної імперської влади). The relationship between peoples, religious and ethnic communities, social classes and economic clans, corporations and individuals are the result of direct contact of their subjects, and bear the imprint of perceptions and stereotypes that formed them about each other. They have a double feature - integration and conflict. This article aims to examine the structure and typology of conflict relations Zaporozhian and Don Cossacks in the 1743-1775. A systematic analysis of the entire set of conflicts to determine not only the mechanisms of emergence and escalation of the conflict, but their functions. Along with destructive features that are well documented, each mizhkozatskyy conflict carried the possibility of constructive solutions to problems encountered in public life. Thus, we distinguish the following positive features Zaporozhya-Don conflicts: • information (due to conflicts, the Zaporozhian and Don officers received information about the immediate problem, it positively influenced the practice of protecting the rights and liberties of the Cossacks in the fight with the neighbors, and the Don Cossacks succeeded his experience in dealing with conflicts mizhkozatskyh used in practice to combat attacks on military land Russian fortresses and other neighbors); • security (conflicts led to partial discharge of tension between Cossacks and stems) • integrative (conflicts intensified intra cohesion Zaporozhye and Don Cossacks, indicated the need to jointly defend their interests); • legislative (due to settlement of a number of conflicts, particularly in the years 1746-1752. Revaluation held norms and values of relations, which led to the total improvement); • incentive (incentive conflicts provide development management system within the Cossack communities become agents of change in regional policy and have adjusted their attitude to the central imperial power). Don Cossack Starshyna was better adapted to the conditions of the Russian Empire. She used the rational methods and means to achieve their goals, which in those conditions in most cases succeeded. Support ethnically Russian Empire Don Cossacks shows that the Cossacks, and with it the Ukrainian general were a foreign body in the body of the empire. Conflicts between Cossacks and stems showed differences in the two types of paradigm Cossack communities, the two Slavic nations. There was a clash not only representatives of the two oligarchic clans, but also the ideological struggle between two models of the Cossacks, two social and national models. Formal victory Don model indicates a higher level of adaptation to the absolutist form of government, the bureaucracy rules. In fact, the victory Zaporozhian settlement model and development of the southern lands of the «public» (Village) Don and then fixing of the disputed land for Ukraine, Zaporozhya witnessed a historic victory in numerous disputes XVIII. Системный анализ материалов, на которых написана статья, всей совокупности конфликтов позволяет определить не только механизмы возникновения и эскалации конфликтной ситуации, но и их функции. Наряду с деструктивными функциями, которые являются достаточно очевидными, каждый конфликт нес в себе возможность конструктивного решения проблем, возникающих в общественной жизни. Так, выделим следующие положительные функции запорожско-донских конфликтов: информационная; охранная; интегративная; нормо-образовательная (вследствие решения ряда конфликтов, в частности, в 1746-1752 гг. состоялась переоценка норм и ценностей мижкозацьких взаимоотношений, привело к общему их улучшения); стимулирующая (конфликты оказали стимул развитию системы управления внутри казачьих сообществ, стали движущей силой изменений в региональной политике и скорректировали их отношение к центральной имперской власти).